Ptychopteridae, a family of flies (Diptera) new to the Philippine Islands with the description of a new species - Paramonov, Nikolay M. (Zootaxa, 2013)
Ptychoptera (Ptychoptera) noonadani sp. nov. is described and is the first record of family Ptychopteridae from the Phil-ippine Islands. A key to males of all Ptychoptera species recorded from the Malay archipelago is presented.